2018
DOI: 10.15171/apb.2018.080
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Predictive Value of Serum Bilirubin in Patients with Ischemic Stroke: A Prospective Descriptive Analytical Study

Abstract: Purpose: In all types of ischemic stroke, especially in the acute phase, excessive oxidative stress causes structural and functional damage to the brain. This may play a major role in the pathophysiology of the brain damage. Higher serum levels of bilirubin have therapeutic effects in oxidative stress-induced stroke. Nevertheless, role of increased serum levels of bilirubin in the acute phase of ischemic stroke is ccontroversial.Methods: This study was a cross-sectional prospective descriptive study conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
0
17
1
Order By: Relevance
“…Evidence on the prognostic value of serum bilirubin in ischemic stroke is still controversial. The Acute Inflammatory Stroke Study with 142 stroke patients and the a cross-sectional prospective descriptive study with 275 ischemic stroke patients showed serum bilirubin level was significantly associated with mortality in the acute phase of ischemic stroke patients [ 4 , 5 ]. Study of Kurzepa et al with 43 patients reported that level of TBIL in the acute phase of ischemic stroke proved to be a bad prognostic factor for both early neurological status and for long term neurological functions measured at 3 months after stroke onset [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on the prognostic value of serum bilirubin in ischemic stroke is still controversial. The Acute Inflammatory Stroke Study with 142 stroke patients and the a cross-sectional prospective descriptive study with 275 ischemic stroke patients showed serum bilirubin level was significantly associated with mortality in the acute phase of ischemic stroke patients [ 4 , 5 ]. Study of Kurzepa et al with 43 patients reported that level of TBIL in the acute phase of ischemic stroke proved to be a bad prognostic factor for both early neurological status and for long term neurological functions measured at 3 months after stroke onset [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated the positive correlation between TBIL, DBIL and the NIHSS of ischemic stroke patients [54,55]. It was also found that TBIL, DBIL and IBIL levels were signi cantly associated with mortality in AIS patients [56]. Further large-scaled studies are needed to clarify this issue.…”
Section: Subgroup and Meta-regression Analysesmentioning
confidence: 92%
“…From 73 patients with LAA stroke, Wang et al found that the level of TBIL (direct bilirubin (DBIL), indirect bilirubin) was positively associated with stroke severity (NIHSS score) on day 1, 7 and 14, as well as with poor functional outcomes (mRS score) on day 30 55. Other studies also showed that both levels of serum DBIL and TBIL were positively correlated with stroke severity3 56–58 and poor prognoses59 60 in AIS. Another study reported that patients with higher DBIL levels had significantly greater NIHSS scores on admission than those with lower levels of DBIL, whereas TBIL did not show this type of correlation 61.…”
Section: Serum Bilirubin and Ischaemic Stroke Outcomesmentioning
confidence: 99%
“…It was proposed that stroke severity at admission was a strong confounding factor influencing the prognosis of stroke patients,67 suggesting that initial stroke severity may be a mediator of the relationship between the level of serum bilirubin and the prognosis of IS patients. Based on these findings, it is possible that a high level of bilirubin might be associated with improved stroke outcome35 after excluding stroke patients with liver dysfunction, adjusting for alcohol intake and initial stroke severity 53–55 59 60…”
Section: Serum Bilirubin and Ischaemic Stroke Outcomesmentioning
confidence: 99%